Post-9/11 War Deployments Increased Crime among Veterans - Resul Cesur; Joseph J. Sabia; Erdal Tekin (Institute of Labor Economics (IZA), 2020)
Several high-profile news stories have linked post-September 11 (9/11) combat service to violent crime among veterans. Nevertheless, there is scant causal evidence for this claim. We exploit the administrative procedures by which U.S. Armed Forces senior commanders conditionally randomly assign active duty servicemen to overseas deployments to estimate the causal impact of modern warfare on crime. Using data from two national surveys and a unified framework, we find consistent evidence that post-9/11 combat service substantially increased the probability of crime commission among veterans. Combat increases the likelihood of property and violent crime, arrest, gang membership, trouble with police, and punishment under the Uniform Code of Military Justice. Back-of-the-envelope calculations suggest that post-9/11 combat exposure generated approximately 26.7 billion in additional crime costs. Finally, we document descriptive evidence that Traumatic Brain Injury and Post-Traumatic Stress Disorder (PTSD) may be important mechanisms to explain post-9/11 combat-induced increases in crime.
Keywords: H56; K14; 330; post-9/11 combat service; military deployments; war; crime; arrests